2020
DOI: 10.15252/emmm.202012560
|View full text |Cite
|
Sign up to set email alerts
|

SARS ‐CoV‐2, bacterial co‐infections, and AMR : the deadly trio in COVID ‐19?

Abstract: Respiratory viral infections are well known to predispose patients to bacterial co‐infections and superinfections. Still, there is limited reference to these in COVID‐19. Do co‐infections play a significant role during COVID‐19? What is the impact of antimicrobial resistance?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
132
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(145 citation statements)
references
References 23 publications
7
132
0
6
Order By: Relevance
“…The H5N1 microRNA increases cytokine production and mouse mortality by blocking PCBP2 which is a suppressor of RIG-1/MAVS (Li et al, 2018b). SARS-CoV and other respiratory viruses have similar non-structural proteins involved in modulating interferon and other innate host responses (Liu et al, 2014;Bengoechea and Bamford, 2020).…”
Section: Viral Factors Leading To Severe Iav Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The H5N1 microRNA increases cytokine production and mouse mortality by blocking PCBP2 which is a suppressor of RIG-1/MAVS (Li et al, 2018b). SARS-CoV and other respiratory viruses have similar non-structural proteins involved in modulating interferon and other innate host responses (Liu et al, 2014;Bengoechea and Bamford, 2020).…”
Section: Viral Factors Leading To Severe Iav Infectionmentioning
confidence: 99%
“…It is not fully clear yet the extent to which these similar factors result in bacterial superinfection in severe COVID-19 patients. Although not highlighted in initial studies it appears that bacterial superinfections due occur in COVID-19 (Bengoechea and Bamford, 2020;Cucchiari et al, 2020;Somers et al, 2020). The risk of this was found to be increased by use of Tocilizumab (IL-6 blocker) in ventilated COVID-19 patients from 26 to 54% of patients, despite apparent overall benefit of the treatment (Somers et al, 2020).…”
Section: Evidence That Myeloid Cells Can Be Both Helpful and Harmfulmentioning
confidence: 99%
“…Therefore, the need for antibiotic treatment should be promptly evaluated and discontinued when not appropriate. 20 Nevertheless, there is a lack of studies conducted in Egypt to characterize the disease and predict its severity. Therefore, we aimed in this study to demonstrate the clinical, laboratory, radiological characteristics, and the predictors of severity of COVID-19 infection at the initial diagnosis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…While experts have warned of the link between COVID-19 and AMR [3][4][5][6][7][8], studies report conflicting evidence. Several studies-from, in particular, Germany, Italy and the US-have reported outbreaks or an increase in infections with and/or acquisition of multidrug-resistant bacteria during the COVID-19 pandemic [9][10][11][12].…”
mentioning
confidence: 99%